Insulin-like growth factor 2 mRNA binding protein 2 promotes aerobic glycolysis and cell proliferation in pancreatic ductal adenocarcinoma via stabilizing GLUT1 mRNA. (15th May 2019) - Huang, Shan; Wu, Zheng; Cheng, Yunyun; Wei, Wenzhen; Hao, Linlin
Abstract: Insulin-like growth factor 2 mRNA binding protein 2 (IGF2BP2) is a member of the IGF2BP protein family consisting of IGF2BP1~3 with the capacity of binding to many transcripts and regulating RNA stability, localization, and translation. In this study, we discovered that expression of IGF2BP2 was upregulated and led to a poor prognosis in pancreatic ductal adenocarcinoma (PDAC). IGF2BP2 protein was gradually elevated from normal pancreas, pancreatic intraepithelial neoplasia to PDAC in an LSL- Kras G12D/+ ;LSL- Trp 53 R172H/+ ;Pdx1- Cre mouse model. Furthermore, we demonstrated that IGF2BP2 promoted aerobic glycolysis and PDAC cell proliferation through directly binding to and stabilizing GLUT1 mRNA. In summary, our study unveiled an important role of IGF2BP2 in PDAC development by modulating aerobic glycolysis and as a potential therapeutic target for PDAC treatment.